Aerodynamic Evaluation of Flapping Wings with Leading-Edge Twisting - Lung-Jieh Yang; Vivek Jabaraj Joseph; Yuan-Lung Lo; Wen-Tzu Tang; Balasubramanian Esakki; Saravana Kompala; Paritala Veeranjaneyulu (Biomimetics, 2023)
The purpose of the current study is to emphasize the characteristics and phenomena of leading-edge twisting in flapping wing vehicles. A fused deposition modeling (FDM) 3D printing method is applied to develop the flapping mechanisms with bevel gears to achieve the leading-edge twisting. Three flapping mechanisms were developed, including simple flapping only (type-A1: normal servo mechanism), flapping with continuous leading-edge twisting (type-B: servo-bevel gear mechanism), and flapping with restricted leading-edge twisting via mechanical stoppers (type-B1: servo-bevel gear mechanism with adjustable mechanical stoppers). Utilizing a low-speed wind tunnel, the aerodynamic performances of these mechanisms are examined by extracting their lift and net thrust forces. The wind tunnel testing data showed that the flapping with restricted leading-edge twisting via mechanical stoppers (type-B1) showed better performance than the simple flapping (type-A1) by 32.9%, and also better performance than the flapping with continuous leading-edge twisting (type-B) by 64%. Next, MATLAB software was used to create the 3D wing surfaces from the instantaneous stereophotography Kwon3D trajectories to fully sketch the leading-edge twisting features. The 2D airfoil cut sections at the mean aerodynamic chord at different stroke moments depict the instantaneous angles of attack to justify the aforementioned wind tunnel testing data and it was verified using a theoretical trajectory model. This comprehensive study using the 3D-printed mechanisms is well suited for the quantitative evaluation of the lift contribution from leading-edge twisting.